What do you mean, ‘megafire’? - Linley, Grant D.; Jolly, Chris J.; Doherty, Tim S.; Geary, William L.; Armenteras, Dolors; Belcher, Claire M.; Bliege Bird, Rebecca; Duane, Andrea; Fletcher, Michael‐Shawn; Giorgis, Melisa A.; Haslem, Angie; Jones, Gavin M.; et al. (Global ecology and biogeography, 2022)
Background ‘Megafire’ is an emerging concept commonly used to describe fires that are extreme in terms of size, behaviour, and/or impacts, but the term’s meaning remains ambiguous. Approach We sought to resolve ambiguity surrounding the meaning of ‘megafire’ by conducting a structured review of the use and definition of the term in several languages in the peer‐reviewed scientific literature. We collated definitions and descriptions of megafire and identified criteria frequently invoked to define megafire. We recorded the size and location of megafires and mapped them to reveal global variation in the size of fires described as megafires. Results We identified 109 studies that define the term ‘megafire’ or identify a megafire, with the term first appearing in the peer‐reviewed literature in 2005. Seventy‐one (~65%) of these studies attempted to describe or define the term. There was considerable variability in the criteria used to define megafire, although definitions of megafire based on fire size were most common. Megafire size thresholds varied geographically from > 100–100,000 ha, with fires > 10,000 ha the most common size threshold (41%, 18/44 studies). Definitions of megafire were most common from studies led by authors from North America (52%, 37/71). We recorded 137 instances from 84 studies where fires were reported as megafires, the vast majority (94%, 129/137) of which exceed 10,000 ha in size. Megafires occurred in a range of biomes, but were most frequently described in forested biomes (112/137, 82%), and usually described single ignition fires (59% 81/137). Conclusion As Earth’s climate and ecosystems change, it is important that scientists can communicate trends in the occurrence of larger and more extreme fires with clarity. To overcome ambiguity, we suggest a definition of megafire as fires > 10,000 ha arising from single or multiple related ignition events. We introduce two additional terms – gigafire (> 100,000 ha) and terafire (> 1,000,000 ha) – for fires of an even larger scale than megafires.